Discovery of a Bacterial 5-Methylcytosine Deaminase - Hitchcock, Daniel S. (Biochemistry, 2014)
[Image: see text] 5-Methylcytosine is found in all domains of life, but the bacterial cytosine deaminase from Escherichia coli (CodA) will not accept 5-methylcytosine as a substrate. Since significant amounts of 5-methylcytosine are produced in both prokaryotes and eukaryotes, this compound must eventually be catabolized and the fragments recycled by enzymes that have yet to be identified. We therefore initiated a comprehensive phylogenetic screen for enzymes that may be capable of deaminating 5-methylcytosine to thymine. From a systematic analysis of sequence homologues of CodA from thousands of bacterial species, we identified putative cytosine deaminases where a “discriminating” residue in the active site, corresponding to Asp-314 in CodA from E. coli, was no longer conserved. Representative examples from Klebsiella pneumoniae (locus tag: Kpn00632), Rhodobacter sphaeroides (locus tag: Rsp0341), and Corynebacterium glutamicum (locus tag: NCgl0075) were demonstrated to efficiently deaminate 5-methylcytosine to thymine with values of k(cat)/K(m) of 1.4 × 10(5), 2.9 × 10(4), and 1.1 × 10(3) M(–1) s(–1), respectively. These three enzymes also catalyze the deamination of 5-fluorocytosine to 5-fluorouracil with values of k(cat)/K(m) of 1.2 × 10(5), 6.8 × 10(4), and 2.0 × 10(2) M(–1) s(–1), respectively. The three-dimensional structure of Kpn00632 was determined by X-ray diffraction methods with 5-methylcytosine (PDB id: 4R85), 5-fluorocytosine (PDB id: 4R88), and phosphonocytosine (PDB id: 4R7W) bound in the active site. When thymine auxotrophs of E. coli express these enzymes, they are capable of growth in media lacking thymine when supplemented with 5-methylcytosine. Expression of these enzymes in E. coli is toxic in the presence of 5-fluorocytosine, due to the efficient transformation to 5-fluorouracil.